2008
DOI: 10.1037/0096-1523.34.5.1108
|View full text |Cite
|
Sign up to set email alerts
|

Object substitution masking: When does mask preview work?

Abstract: When a target is surrounded by a four-dot mask pattern that persists after the target disappears, target identification is worse than when the mask terminates with the target. This masking effect has been attributed to Object Substitution Masking (OSM). Previewing the four-dot mask attenuated OSM. This study investigated specific situations in which mask preview was (or was not) effective in attenuating masking. In Experiment 1, the interstimulus interval (ISI) between previewed mask offset and target presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…This account predicts that masking is strongly increased by manipulations that encourage and reduced by manipulations that discourage the inference the target and mask reflect a continuing object over time. Consistent with this, when the target and mask appear in the same versus different colours it exacerbates and mitigates masking respectively (Goodhew et al, 2015;Lleras & Moore, 2003;Luiga & Bachmann, 2008; Moore placeholder objects at the locations of targets and distractors reduce masking, even when these are neither predictive of target location nor reveal key target features (such as the side of the gap) (Gellatly, Pilling, Carter, & Guest, 2010;Guest et al, 2012;Lim & Chua, 2008). Such manipulations facilitate the system characterising the target and mask as distinct objects.…”
mentioning
confidence: 69%
“…This account predicts that masking is strongly increased by manipulations that encourage and reduced by manipulations that discourage the inference the target and mask reflect a continuing object over time. Consistent with this, when the target and mask appear in the same versus different colours it exacerbates and mitigates masking respectively (Goodhew et al, 2015;Lleras & Moore, 2003;Luiga & Bachmann, 2008; Moore placeholder objects at the locations of targets and distractors reduce masking, even when these are neither predictive of target location nor reveal key target features (such as the side of the gap) (Gellatly, Pilling, Carter, & Guest, 2010;Guest et al, 2012;Lim & Chua, 2008). Such manipulations facilitate the system characterising the target and mask as distinct objects.…”
mentioning
confidence: 69%
“…Furthermore, the near-ceiling level accuracy they observed for set size one for pre-cue durations beyond zero mean their interaction was most likely artifactual, an argument that applies also to the study by Germeys et al (2010). Moreover, as Argyropoulos et al noted, the introduction of an asynchrony between target and mask onsets is known to reduce OSM even where the asynchrony is uninformative as a spatial cue (Gellatly et al, 2010;Guest et al, 2012;Lim & Chua, 2008;Neill et al, 2002;Tata & Giaschi, 2004). Indeed this temporal asynchrony effect seems to occur because it prompts the visual system to individuate the target as a separate object independent from the mask, a finding consistent with the object updating hypothesis account of OSM (Lleras & Moore, 2003;Moore & Lleras, 2005).…”
Section: Exogenous Spatial Pre-cueing Reliably Modulates Object Procementioning
confidence: 95%
“…Instead of presenting the local precue continuously during the entire SOA, the four-dot precue was Xashed brieXy at the start of the SOA (e.g., with an SOA of 150 ms, the cue was Xashed for 33 ms followed by a 117-ms interstimulus interval and then the target-plus-mask display). However, recently Lim and Chua (2008) showed that a brief preview of the mask followed by both short and longer interstimulus intervals attenuates OSM. Given these considerations, we opted for a brieXy Xashed outline square instead of a four-dot precue.…”
Section: Experiments 1: Exogenous Precueingmentioning
confidence: 98%